A Phenomenological Study on Meaningful Learning and Worship Awareness in Islamic Religious Education - Muntaha; Hunainah; Supriadi (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
In Islamic Religious Education (IRE), learning is expected to shape worship awareness and spiritual consciousness, yet many classrooms still rely on rote memorization and routine rituals. This study examines how Ausubel’s meaningful learning principles, reinterpreted through an Islamic ontological lens, can nurture adolescents’ daily worship awareness. Using a phenomenological qualitative design, data were gathered through observation, in-depth interviews, and documentation at SMP IT Sahabat Alam Palangka Raya. The findings indicate five meaningful-learning practices in IRE: linking lessons to students’ lived experiences, sequencing content contextually, employing reflective storytelling, using advance organizers, and facilitating post-practice reflection. These practices strengthened students’ understanding of worship while fostering sincerity (ikhlas) and inner awareness, reflected in more voluntary worship habits, deeper appreciation of worship meanings, and improved moral discipline. Teacher exemplarity, a reflective school culture, and structured worship routines further supported this growth, although limited instructional time and uneven teacher training remained challenges. Overall, meaningful learning in IRE functions not only to enhance comprehension but also to cultivate taqwa-oriented character through reflective and experiential engagement with worship.